BLOOD SMEAR EVALUATION OF BALI DUCKS SAMPLED FROM TRADITIONAL FARMING SYSTEMS IN BALI - Haryono Utama, Iwan; -, Sugiyarto; Kendran, Anak Agung Sagung; Pasti Apsari, Ida Ayu; Suarsana, I Nyoman; Krisna Erawan, I Gusti Made; Ayu Mirah Adi, Anak Agung; Oka Winaya, Ida Bagus; Hayashi, Yoshihiro (Jurnal Veteriner, 2008)
Research to confirm the abnormalities of blood corpuscles in Bali ducks based on blood smear examination has been conducted. The research samples consisted of 105 ducks from various regencies in Bali. The blood smear examination was conducted by the method described in this literature and the data was collected and tabulated by means of the descriptive method. Erythrocyte abnormalities were: polychromasia (61.9%), anisocytosis (17.1%), poikilocytosis (21.0%). Abnormalities associated with leukocyte composition were: Lymphopenic (46.7%); Heterophylic (44.8%); Heteropenic (3.8%), also Thrombocyto penia (2.9%) was present in 105 ducks. In conclusion 61,9% ducks examined deal with regenerative anaemia. They also have some blood abnormalities such as basophylia, eosinophylia, heterophylia, heteropenia, lymphopenia, and monocytosis.
Keywords: blood smear, ducks